Effect of triazoles and IBA on growth of Adhatoda vasica cuttings - Panneerselvam, M. Gnana Mani, R. (Journal of Ecobiotechnology, 2015)
In the present investigation, triadimefon (TDM), Hexaconazole (HEX) and IBA treatments in Adhatoda vasica plants were done in order to study the comparative effects of traditional as well as non-traditional growth regulators on the rooting behaviour. The traditional growth regulator selected was IBA and non-traditional one was HEX and TDM. TDM, HEX treatments decreased the height of the plant and IBA increased the height of the plant.Â The leaf area also reduced under triazole treatments where as leaf area increased under IBA treatment. The root growth was significantly increased at all stages of growth with TDM, HEX and IBA treatments. Towards maturity, the whole plant fresh weight increased considerably with TDM, HEX and IBA treatments in Adhatoda vasica plants when compared to control.Â The dry weight also increased in TDM, HEX and IBA treatments due to the increase in root growth. These preliminary results prove TDM and HEX as potential growth regulators which can be used to enhance the rooting of Adhatoda vasica, thereby make the propagation easy in this medicinal plant.